Electron Density Profiles in the Upper Ionosphere of Mars From 11 Years of MARSIS Data: Variability Due to Seasons, Solar Cycle, and Crustal Magnetic Fields. Issue 4 (23rd April 2019) - Duru, F.; Brain, B.; Gurnett, D. A.; Halekas, J.; Morgan, D. D.; Wilkinson, C. J.
Abstract: The Mars Advanced Radar for Subsurface and Ionosphere Sounding on board the Mars Express spacecraft measures the frequency of local plasma oscillations, which can be used to determine electron densities local to the spacecraft. This paper provides an overview of electron densities in the upper Martian ionosphere, obtained by investigating over 400, 000 ionograms, during the course of about 11 years, corresponding to a full solar cycle. The data cover wide latitude and longitude ranges, 180° of solar zenith angle (SZA), and altitudes from about 250 to 1, 550 km. The electron density profiles show large fluctuations within each orbit and also for any given altitude and SZA range. However, the median electron density is almost constant on the dayside at a fixed altitude range, with the exception of a dip at around 30° SZA, at altitudes between 300 and 600 km. A sudden drop in density is observed as the terminator is approached from the dayside. For a fixed SZA range, the median electron density decreases exponentially with increasing altitude. The high‐altitude scale height is composed of two exponential functions of SZA joined near the ionospheric terminator. The e ‐folding height changes between 45 and 214 km from the subsolar point up to 120°, corresponding to effective temperatures between about 165 and 780 K. Solar activity has a clear effect on the median electron densities above 500 km and on e ‐folding height. The median electron density is higher during northern winters, as well as above regions of strong crustal fields on the dayside. Key Points: Electron density increases with decreasing altitude with an e ‐folding height changing between 45 and 120 km from 0 to 120 degrees of SZA Data for a full solar cycle show that the average electron density values are directly related to the solar activity Electron densities are higher during northern winters and above strong crustal magnetic fields on the dayside